DESAIN PERENCANAAN MASTER PLAN PADA UPT. PERPUSTAKAAN UNIVERSITAS SERAMBI MEKKAH ACEH - Sri Wahyuni (IAIN Batusangkar, 2020)
The library of Serambi-Mekkah University is one of the main libraries at the Aceh College which serves all academic communities. In facilitating library service activities, it is necessary to use good information technology with strategic planning as outlined in a Master Plan in a form. Preparing the Master Plan aims to provide long-term guidelines to be aligned by aspects of the library field and provide tangible benefits to the library in achieving its vision and mision from the design of information system. The research method used in developing information systems at the Serambi Mekkah University Library Aceh uses needs analysis and designing library software. The library of Serambi-Mekkah University Aceh uses a diagram model (use case) which is a complete description of the interactions between actors with designing and creating information systems.